2018
DOI: 10.3233/wor-182816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body vibration on spinal proprioception in healthy individuals

Abstract: BACKGROUND: Low back pain (LBP) is a common health problem with high reoccurrence rate. As patients with LBP are often found to be proprioception impaired, new proprioception exercises should be explored. Whole body vibration (WBV) has been proven to improve muscle function and proprioception. OBJECTIVE: The aim of this study was to determine the effects of WBV on spinal proprioception when WBV was administered in standing and seated postures. METHODS: Twenty healthy male individuals (mean age: 23.2 ± 1.2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…The results of this study showed that there were no significant positive effects on postural control as detected by posturography, for sensorimotor physiotherapeutic training, Galileo ® training, or Posturomed ® training. This is contrary to the majority of studies that demonstrated significant postural improvements following sensorimotor physiotherapeutic training and sensorimotor vibration training [5,24,26,[38][39][40][41][42][43][44]. However, it is difficult to relate the results of these studies to the current study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The results of this study showed that there were no significant positive effects on postural control as detected by posturography, for sensorimotor physiotherapeutic training, Galileo ® training, or Posturomed ® training. This is contrary to the majority of studies that demonstrated significant postural improvements following sensorimotor physiotherapeutic training and sensorimotor vibration training [5,24,26,[38][39][40][41][42][43][44]. However, it is difficult to relate the results of these studies to the current study.…”
Section: Discussioncontrasting
confidence: 84%
“…At the same time, vibrational stimuli also have inhibitory effects on the neuromuscular system [22]. A significant improvement in proprioceptive properties in the lumbar region [23] as well as a reduction in pain intensity and an increase in postural stability in patients with chronic back pain [24][25][26] have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…WBVT has shown effects on body posture, flexibility, proprioception (TTDPM in patients with osteoarthritis), coordination and muscle power. [59][60][61] It has been promoted as an effective method to induce a reflex muscle contraction in subjects with difficulties to evoke voluntary contractions. 62 The mechanism behind the improvements may be that the vibration stimuli excite muscle spindles, and activate the tonic vibration reflex, which acts on alpha-motor neurons.…”
Section: Mechanisms Underpinning Nt Following Aclrmentioning
confidence: 99%
“…Whole-body vibration (WBV) is a training and rehabilitation system that mainly uses the technology of vibrating platforms and that has been demonstrating several positive therapeutic and physiological effects, such as improvement of muscle strength, blood circulation, blood perfusion, muscle performance, bone density, neuromuscular response, increased electromyographic signal (EMG), increased neuromuscular system response, improved sports performance, muscle tone, muscle flexibility, proprioception, muscle tone, among others (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). This system has been widely used and studied due to its easy application, being a non-invasive method, with immediate acute effects, with short sessions, being widely disseminated in sports and rehabilitation centers, apart from having literary support on its effects.…”
Section: Introductionmentioning
confidence: 99%